Network pharmacology-based strategy to investigate the active ingredients and molecular mechanisms of Scutellaria Barbata D. Don against radiation pneumonitis. Issue 47 (24th November 2021) - Sun, Ping-Yi; Wang, Ai-Shuai; Zhang, Zhen-Fei; Zhang, Yan-Li; Zheng, Xin
Abstract: Introduction: Herbal medicines combined with radiotherapy significantly reduced the incidence of radiation pneumonitis (RP), and the Scutellaria barbata D. Don (SBD) is a perennial herb that has been reported to protect against radiation-induced pneumonitis. However, the exact molecular mechanism is not known. The objective of this research was to investigate the against radiation pneumonitis ingredients and their functional mechanisms in SBD . Methods: Based on the network pharmacology approaches, we collected active ingredients and target genes in SBD against RP through Traditional Chinese Medicine System Pharmacology (TCMSP) Database, and the "Herb–Ingredients–Target Genes–Disease" Network was constructed by using of Cytoscape. STRING analysis was performed to reveal the protein-protein interactions, and then we applied enrichment analysis on these target proteins, gene function, and pathways. Results: A total of 18 ingredients in SBD regulate 65 RP related target proteins, which show that quercetin, luteolin, baicalein, wogonin may be the key active ingredients, while IL6, AKT1, VEGFA, MMP9, CCL2, prostaglandin-endoperoxide synthase 2 (PTGS2) (cyclooxygenase-2 [COX-2]), CXCL8, IL1B, mitogen-activated protein kinase (MAPK1), and IL10 were identified as critical targets. Besides, the results of Gene Ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that predicted targets of SBD are mostly associated with the pathological process of oxidative stress and inflammation. AGE- Receptor of Advanced Glycation Endproducts (RAGE) signaling pathway in diabetic complications, IL-17 signaling pathway, hypoxia-inducible factor-1 (HIF-1) signaling pathway, NF-kappa B signaling pathway might serve as the principal pathways for RP treatment. Conclusion: In our study, the pharmacological and molecular mechanism of SBD against RP was predicted from a holistic perspective, and the results provided theoretical guidance for researchers to explore the mechanism in further research. Abstract : Supplemental Digital Content is available in the text